The lectin pathway of complement activation - Krarup, A (2007)
The complement system is an important immune system mechanism involved in both the recognition and elimination of invading pathogens. It is activated by three different pathways: The classical pathway, which relies on binding of C1, and results in the cleavage of C4 and C2 through activation of C1r and C1s; the alternative pathway that relies on the spontaneous hydrolysis of C3 and the lectin pathway. The lectin pathway is activated by binding of Mannan-binding lectin (MBL) or the ficolins (L-ficolin, H-ficolin and M-ficolin) to microbial binding motifs, and the subsequent activation of the MBL-associated serine proteases (MASP) 1/ 2/ 3. Of these MASP2 has been identified as the enzyme responsible for the activation of complement by C4 and C2 cleavage. The work presented here will focus on four different aspects of the lectin pathway: specificity and stoichiometry of the L-ficolin protein complex, expression of H-ficolin, substrate characterization for MASP1 and investigation of the prothrombin activation potential of MASP2. L-ficolin binding specificity was investigated using glycan array technology, and it was found that L-ficolin, instead of recognizing single monosaccharides like MBL, instead binds to extended oligosaccharide structures. The binding to these was dependent not only on the presence of acetyl groups, but also on their orientation in space. It was also found that L-ficolin in serum is found as a multimeric protein complex composed of 18 polypeptide chains and associated with one MASP dimer. The expression of H-ficolin resulted in the generation of a stable mammalian cell line producing oligomerized and biologically functional H-ficolin. MASP1 substrate specificity was investigated by two different procedures. Firstly fractionated plasma was subjected to MASP1 treatment in an attempt to identify a plasma protein substrate. This did not yield any substrate candidates, since only cleavage of the protease inhibitor α-2-macroglobulin could be detected. Additionally the thrombin-like activity of MASP1 was investigated through cleavage experiments done with factor XIII and fibrinogen. These experiments showed that the factor XIII cleavage site for MASP1 and thrombin is identical. This was also found for the fibrinogen β-chain but not for the α-chain showing that MASP1 interaction with fibrinogen is distinct from that of thrombin. An earlier observation that MASP2 was capable of activating prothrombin and generating thrombin was further characterized. Here it was shown that the activation of prothrombin by MASP2 is identical to that by factor Xa, which is the enzyme undertaking this role in the coagulation system, and that the activation can result in deposition of fibrin on the surface upon which MASP2 is bound. The prothrombin activation potential of MASP2 was also utilized to develop a new MASP2 activity assay, which was shown to be capable of measuring MASP2 activity, when MASP2 is bound, via MBL (or L-ficolin) to appropriate surfaces.